2017
DOI: 10.1186/s12933-017-0517-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of canagliflozin in patients with type 2 diabetes based on history of cardiovascular disease or cardiovascular risk factors: a post hoc analysis of pooled data

Abstract: BackgroundTreatment of patients with type 2 diabetes mellitus (T2DM) and a history of cardiovascular (CV) disease or CV risk factors may present clinical challenges due to the presence of comorbid conditions and the use of concomitant medications. The sodium glucose co-transporter 2 inhibitor, canagliflozin, has been shown to improve glycaemic control and reduce body weight and blood pressure (BP) with a favourable tolerability profile in a broad range of patients with T2DM. This post hoc analysis assessed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
4
24
0
Order By: Relevance
“…Furthermore, many studies demonstrated that SGLT2is decrease body weight, blood pressure, and TG. These results support the hypothesis that SGLT2is have specific cardioprotective effects 16,17) . Further studies are needed to understand the cardioprotective effects of SGLT2is.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, many studies demonstrated that SGLT2is decrease body weight, blood pressure, and TG. These results support the hypothesis that SGLT2is have specific cardioprotective effects 16,17) . Further studies are needed to understand the cardioprotective effects of SGLT2is.…”
Section: Discussionsupporting
confidence: 88%
“…Recent randomized placebo-control studies found that sodium-dependent glucose transport 2 inhibitors (SGLT2is) (e.g., canagliflozin) reduced cardiovascular events in addition to their effect as antidiabetic drugs [11][12][13][14] . Previous studies demonstrated that SGLT2is reduce blood glucose levels, blood pressure, and body weight in T2DM patients, all of which play roles in atherogenesis 11,[15][16][17] . However, the mechanisms by which SGLT2is prevent cardiovascular events are not completely understood and need to be explored to achieve better treatment in T2DM patients with risk of cardiovascular events.…”
Section: Vascular Reactivity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our study cohort, patients with heart failure are at risk for fluid overload and extracellular water accumulation, leading to hydropic decompensation and hospitalization [47]. Treatment with SGLT2 inhibitors has been shown to reduce this risk [12] and was found to be safe and efficient in patients with type 2 diabetes and different stages of cardiovascular disease [48]. SGLT2 inhibition could lead to a sustained correction of fluid accumulation in patients starting with an elevated level of overhydration and extracellular water.…”
Section: Discussionmentioning
confidence: 78%
“…In a pooled data analysis of four clinical trials with canagliflozin, both 100 and 300 mg doses were associated with an increased frequency of osmotic diuresis symptoms (eg, increased urine volume and frequency) yet symptoms related to a reduction of vascular volume (eg, orthostatic and postural hypotension) were not increased by either dose. In an analysis of several trials with empagliflozin, events related to volume depletion were infrequent (1.8%) yet significantly increased in older patients over aged 75 years…”
Section: Adverse Effects Related To Either Blood Glucose Lowering or mentioning
confidence: 98%